In-office Eustachian tube balloon dilation under local anesthesia as a response to operating room restrictions associated with the COVID-19 pandemic - Sheppard, Sean C.; Beckmann, Sven; Caversaccio, Marco; Anschuetz, Lukas (Frontiers in Surgery, 2023)
Objective: To evaluate the feasibility of local anesthesia for Eustachian tube balloon dilation as an in-office procedure for the treatment of Eustachian tube dilatory dysfunction as a response to the restriction measures of the COVID-19 pandemic. Method: Patients with Eustachian tube dilatory dysfunction refractory to nasal steroids undergoing Eustachian tube balloon dilation in local anesthesia were enrolled in a prospective observational cohort from May 2020 to April 2022. Patients were assessed with the ETDQ-7 score and Eustachian tube mucosal inflammation scale. They underwent clinical examination, tympanometry and pure tone audiometry. Eustachian tube balloon dilation was performed in-office under local anesthesia. Patients perioperative experience was recorded using a 1-10 VAS scale. Results: 30 patients (47 Eustachian tubes) underwent the operation successfully. One attempted dilation was aborded due to anxiety of the patient. Local anesthesia was performed with topical lidocaine and nasal packing for all patients. 3 patients required infiltration of the nasal septum and or tubal nasopharyngeal orifice. Mean time of operation: 5.7 min per Eustachian tube dilation. Mean discomfort during intervention: 4.7 (on a 1-10 VAS scale). All patients returned home immediately after the intervention. The only reported complication was one self-limiting subcutaneous emphysema. Conclusion: Eustachian tube balloon dilation can be performed under local anesthesia and is well tolerated by most patients. No major complications occurred. In order to free operation room capacities, the intervention can be performed in an in-office setting with satisfactory patient feedback.